2012
DOI: 10.1163/156854111x602974
|View full text |Cite
|
Sign up to set email alerts
|

Bursaphelenchus firmae n. sp. (Nematoda: Aphelenchoididae), isolated from Monochamus grandis Waterhouse that emerged from dead firs, Abies firma Sieb. et Zucc.

Abstract: Bursaphelenchus firmae n. sp. is described. This new species was isolated during a field survey of longhorn beetleassociated nematodes. The fourth-stage dispersal (dauer) juveniles of the new species were recovered from dissected bodies (tracheal system) of Monochamus grandis, which emerged from dead logs of Japanese fir, Abies firma, collected from Hachioji, Tokyo, Japan. The new species is mid-sized for the genus, with females 603-828 μm and males 530-698 μm long. Four lateral lines occur on the body surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The 28S D2/D3 tree of Kanzaki et al (2012) suggested that B. trypophloei does not appear to belong to the xylophilus group, although there was no further discussion of position. In this study, the ITS and 28S tree (Figs 5, 6) also show that B. trypophloei is well separated from the xylophilus group but is very close to B. tokyoensis.…”
Section: Discussionmentioning
confidence: 99%
“…The 28S D2/D3 tree of Kanzaki et al (2012) suggested that B. trypophloei does not appear to belong to the xylophilus group, although there was no further discussion of position. In this study, the ITS and 28S tree (Figs 5, 6) also show that B. trypophloei is well separated from the xylophilus group but is very close to B. tokyoensis.…”
Section: Discussionmentioning
confidence: 99%
“…All six species of this group also differ from members of the xylophilus-group by their association with bark beetles (Curculionidae: Scolytinae) as vector insects. In contrast, all species of the xylophilus-group that have a known insect association are associated with long-horned beetles (Coleoptera: Cerambycidae), mainly from the subfamily Lamiinae (Enda & Mamiya, 1972;Mamiya & Enda, 1979;Kanzaki et al, 2000Kanzaki et al, , 2008Kanzaki et al, , 2012Kanzaki & Futai, 2003;Tomalak & Filipiak, 2010). Further research should elucidate the exact relationships of these phylogenetic groups, but the data presently available may suggest that this process could be mediated by differences in ecological associations of closely related nematode species with different groups of insect vectors.…”
Section: Discussionmentioning
confidence: 99%
“…They all are as sociated with larval galleries of bark beetles (Coleoptera: Curculionidae, Scolytinae) and have adult bark beetles as vectors, although transmission of B. tokyoensis from gal leries of Cryphalus fulvus Niijima was not directly ob served (Kanzaki et a l, 2009b). By contrast, in all the re maining Bursaphelenchus species of the xylophilus group which have a known insect association, the vectors are long-homed beetles (Coleoptera: Cerambycidae), mainly from the subfamily Lamiinae (Enda & Mamiya, 1972;Mamiya & Enda, 1979;Kanzaki et al, 2000Kanzaki et al, , 2008Kanzaki et al, , 2012Kanzaki & Futai, 2003;. It re mains to be elucidated whether this distinction is related to different phylogenetic pathways in the nematodes and their insect vectors.…”
Section: Discussionmentioning
confidence: 99%